Method Development and Validation of Acyclovir by UV Spectrophotometric Method - Raja, Badavathu; Haq-Kubra, Mohammad Amatul; Prasanna, Gunaganti Lakshmi; Sri, Bura Naga; Islam, Bakkidul; Chinnaeswaraiah, Maram (Asian Journal of Biological and Life Sciences)
Background: Acyclovir, an antiviral agent active against herpes simplex virus types I and II and varicella zoster, is widely used in pharmaceutical formulations. Existing pharmacopoeial methods employ non-aqueous titration or spectrophotometry at 254 nm. However, simple, rapid, and validated UV spectrophotometric methods for routine estimation are limited. Objectives: To develop and validate a simple, sensitive, and cost-effective UV spectrophotometric method for the quantitative estimation of Acyclovir in bulk and pharmaceutical dosage forms as per ICH Q2 (R1) guidelines. Materials and Methods: Acyclovir standard stock solution (1000 µg/mL) was prepared in distilled water. Working solutions (0.5-30 µg/mL) were scanned, and the wavelength of maximum absorbance (λmax ) was determined at 254 nm. Calibration curves were plotted in the concentration range of 0.5-30 µg/mL. Method validation was performed for assay, linearity, precision, accuracy, robustness, ruggedness, Limit of Detection (LOD), and Limit of Quantification (LOQ). Results: The method showed excellent linearity (R²=0.996) in the concentration range of 0.5-30 µg/mL. Accuracy studies demonstrated percentage recoveries between 98.94% and 100.86%, within pharmacopeial limits (99-101%). Precision studies indicated low %RSD (<2%) for repeatability, intra-day, and inter-day analysis. Robustness and ruggedness tests confirmed stability under small deliberate variations in wavelength, analyst, and conditions. The method exhibited low LOD and LOQ values, indicating high sensitivity. Conclusion: The developed UV spectrophotometric method is simple, rapid, precise, accurate, robust, and cost-effective. It can be successfully applied for routine quality control and estimation of Acyclovir in bulk and tablet dosage forms.
Keywords: Acyclovir; Diazo Coupling; p-Dimethylaminobenzaldehyde; Spectrophotometric determination; Acyclovir; Temperature and Coupling Reaction Time